Malignant Peripheral Nerve Sheath Tumor of the Inguinum and Angiosarcoma of the Scalp in a Child with Neurofibromatosis Type 1 - Marija Milković Periša; Tihana Džombeta; Jasminka Stepan Giljević; Božo Krušlin (Case Reports in Pathology)
Benign and malignant tumors are common in the setting of neurofibromatosis type 1 (NF1). Malignant peripheral nerve sheath tumor (MPNST) and angiosarcoma are rare tumors in children and adolescents and mostly occur in young patients in relation to NF1. Both histological types can be present in the same tumor mass in patients with NF1. We present a case of 12.5-year-old girl with NF1 who first presented with MPNST of the right inguinal region and 1.5 years later with unrelated angiosarcoma of the scalp.